Empirical evidence of faulty credit scoring and business failure in P2P lending - Dongwoo Kim (Global Business & Finance Review (GBFR), 2021)
Purpose: This study attempts to identify the cause of the failure of a platform operator in a P2P lending market, from the perspective of the internal credit rating system. Design/methodology/approach: Data from Moneyauction, the first P2P lending platform in Korea, which led the market for a while and then unexpectedly closed down, was analyzed using a series of binary logistic regression and relative weight analysis methods. The study concentrates on the effect and importance of the self-assessed credit score system used by Moneyauction with regard to investor funding decisions and the actual repayment performance outcomes of borrowers. The predictive power of this self-assessed credit score is also identified. Findings: The findings show that while the internal credit score is considered the most important factor in an investor's funding decision, its importance with regard to a borrower's actual repayment performance is significantly lower compared to other factors. Specifically, the predictability when using a model with an internal credit score with regard to a borrower's repayment performance is inferior to a model without this factor. The findings therefore suggest that low-quality self-assessed credit rating systems may in fact contribute to the failure of individual platforms, even when the market is growing rapidly. Research limitations/implications: A series of business failures in a P2P market in the early stages of growth could make it difficult for the market to grow as a promising means of alternative finance due to the mounting distrust of potential participants and the exodus of existing investors. Therefore, the results of this study may present important issues to be discussed in relation to healthy market growth. The findings of this study are from the special case of Moneyauction in Korea. Thus, there is a limit to generalizing the results in this study, and further research is needed on additional platforms in similar situations in different markets. Originality/value: None of the previous studies on P2P lending markets has investigated individual platform failure cases. Existing studies mainly focus on the statistical significance of the effects of borrower characteristics on investors' decisions or borrowers' repayment performances. This study is also distinct in terms of its methodology in that it goes one step further and discusses the relative importance among all aspects of the borrowers' characteristics.
Keywords: 650; Relative importance; Credit score system; P2P lending; Business failure; Prediction